Formation of the CF radical in comets - De Almeida, A. A.; Boice, D. C.; Andreazza, C. M. [UNESP]; De Araújo, L. F. (IOP Publishing, 2019)
In March 2015 the European Space Agency's Rosetta spacecraft performed a close flyby over the surface of comet 67P/Churyumov-Gerasimenko of just 15 km from the comet center. This comet belongs to the Jupiter family with an aphelion at 5.5 au and a perihelion at 1.25 au. Its orbital period is 6.5 years. The ROSINA (Rosetta Orbiter Sensor for Ion and Neutral Analysis)/DFMS (Double Focusing Mass Spectrometer) instrument on board Rosetta reported the first detection among others of glycine (C2H5NO2) an amino acid, other prebiotic molecules, phosphorus atom (P), and fluoromethylidyne (CF), which is not a stable chemical species but a metastable radical [1]. In the case of phosphorus, the search for the parent (PH3, PH, PO, PN, CP, HCP, HPO, CCP) was unsuccessful although these species have been detected mostly in the interstellar medium [2]. This work reports a study of model-dependent chemical networks, based on several databases such as UMIST and NIST among others, to explain the formation of CF radical in comets from gaseous tetrafluoromethane (CF4).